(untitled) (Revista Brasileira Multidisciplinar, 2026)
The study aimed to carry out a survey of the temporal biodiversity and seasonal occurrence of anuran amphibians that live in fish farms. A total of 7 fish farms were selected and were visited in the two Amazon hydrological seasons, rainy and dry. The search for anuran amphibians was carried out by active search, during the species’ nocturnal vocalization shift, between 6 and 10 pm. A total of 151 specimens were observed in the rainy season and 164 specimens in the dry season, from a total of 16 recorded species distributed in 5 families. The most abundant family was the Leptodactylidae, its most abundant species Leptodactylus petersii and Leptodactylus fuscus, which were found on embankments and in the fish ponds supply channels and in the effluent. Regarding similarity, considering the species per family, the families Leptodactylidae and Hylidae showed the most similar communities (40 and 30%, respectively). there was a strong correlation (r= 0.92) between the abundance of the Leptodactylidae family and environmental conditions of average air temperature and rainfall. While for the Hylidae and Bufonidae families the correlations were weaker (r= 0.62 and 0.44), so that as rainfall increased, the abundance of the Bufonidae family reduced. Inventorying anuran amphibian species living in fish farms is an accessible method for studying environmental quality. This study indicated that fish farms did not influence the abundance, spatial and seasonal distribution of anuran amphibian species. In other words, despite being an artificial environment, the anurans began to occupy and adapt to the new habitat.